2010
DOI: 10.1158/1055-9965.epi-10-0508
|View full text |Cite
|
Sign up to set email alerts
|

N -Acetyltransferase 2 Polymorphisms and Susceptibility to Infant Leukemia with Maternal Exposure to Dipyrone during Pregnancy

Abstract: Background: Maternal exposure to dipyrone during pregnancy has been associated with risk of infant leukemia (IL). N-Acetyltransferase 2 (NAT2) enzyme acetylates dipyrone, resulting in a detoxified metabolite. We performed genotyping to identify the distribution of NAT2 polymorphisms in duo samples from mothers and children previously investigated in a case-controlled study of IL.Methods: Samples from 132 IL, 131 age-matched controls, mothers of cases (n = 86), and mothers of controls (n = 36) were analyzed. PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 16 publications
0
27
1
1
Order By: Relevance
“…A positive association between slow NAT2 alleles and childhood ALL has been reported in a few studies [33][34][35] (Table 1).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…A positive association between slow NAT2 alleles and childhood ALL has been reported in a few studies [33][34][35] (Table 1).…”
Section: Introductionmentioning
confidence: 69%
“…The association observed between childhood ALL and NAT2*5, which is expected to lead to a 'slow' acetylator phenotype, has been reported in two studies based on SNP rs1801280 genotyping [34,35] and one study [33] in which the slow acetylation phenotype was defined by the presence of two slow alleles among NAT2*5A, *5B, *5C, *6A, and NAT2*7B alleles.…”
Section: Discussionmentioning
confidence: 95%
“…Because adverse effects of metamizole seem to be related to factors that modify drug exposure or pharmacokinetics [4][5], it could be hypothesized that variability in metamizole biotransformation may modify the risk of developing adverse effects with this drug. Indirect evidence support this hypothesis, since it has been shown that many patients with hypersensitivity to metamizole are negative to skin testing and to basophil activation with metamizole [6], and that NAT2 slow-acetylation haplotypes, that modify the ability of acetylating AA, are associated with the risk of developing infant leukemia with maternal exposure to dipyrone during pregnancy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is surprising that the only metabolic polymorphism that has been studied with regard to metamizole adverse drug reactions is the acetylation polymorphism [12].…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos epidemiológicos apontam a exposição materna a algumas substâncias químicas durante o período pré-natal como fator de risco para o desenvolvimento de doenças na infância 12,13,14,15,16 , como ocorre com os medicamentos dipirona e diclofenaco, por exemplo. Em investigação sobre fatores de risco para tumor de Wilms segundo exposição materna a dipirona na gestação no Brasil, foi observada uma OR = 10,9 (IC95%: 2,4-50,0) associada a esta exposição 16 .…”
Section: Introductionunclassified